Guiding children's social development and learning : theory and skills - Kostelnik, Marjorie J.; Anne K. Soderma; Alice Phipps Whiren; Michelle Rupiper; Kara Murphy Grogory (United States of America : Cengage Learning, 2015)
This book will give you a foundation of knowledge and skills necessary for guiding children's social development and learning in professional practice.
1. Making a difference in children's lives -- 2. Good beginnings: establishing relationships with infants and toddlers -- 3. Building positive relationships through nonverbal communication -- 4. Promoting children's positive sense of self through verbal communication -- 5. Supporting children's emotional development and learning -- 6. Building resilience in children -- 7. Play as a context for social social development and learning -- 8. Supporting children's peer relationships and friendships -- 9. Influencing children's social development by structuring the physical environment -- 10. Fostering self-regulation in children: communication expectations and rules -- 11. Fostering self-regulation in children: the role of consequences -- 12. Handling children's aggressive behavior -- 13. Promoting prosocial behavior -- 14. Fostering healthy attitudes about sexuality and diversity -- 15. Making ethical judgments and decisions
Includes bibliographical references and index.
Keywords: SOCIAL SKILLS IN CHILDREN; CHILD DEVELOPMENT